The COVID-19 Pandemic Impact on Elementary Students Online Learning Motivation - Gingga Prananda; Yonnie Kharismadewi; Zuhar Ricky; Sonia Yulia Friska (Jurusan PGMI FTIK IAIN Metro Lampung, 2021)
Abstract: The Covid-19 pandemic has frutrated students from various levels of education, including elementary students, the teaching and learning process which is usually carried out in classrooms is now being applied online at home with parents as companions. The aim of this research was to obtain the facts and data about the COVID-19 pandemic impact toward the elementary student’s online learning motivation and to see whether the online learning in elementary levelis effective to be conducted. The research used descriptive research with the qualitative approach done to discover and describe a research object. The population in the research is all of the third-grade students of state elementary schools in Cluster I Abai Siat Dharmasraya, with the total is 4 schools which have 245 students for overall. The survey method used in thin research was the technique of Proportionate Stratified Random Sampling. The research result displayed that Covid-19 has influence partially to ward the student’s online learning motivation in the state elementary schools cluster I Abai Siat Dharmasraya whit the t-acount is about 2.477 while f-table is about 1.977, and it also impacts simultaneously whit the number of f-count greater than f-table that is 5.68 > 2.67. Keywords : Covid-19 pandemic, online learning motivation Abtrak: Pandemi Covid-19 telah meresahkan pelajar dari berbagai jenjang pendidikan, tidak terkecuali siswa tingkat dasar, proses belajar mengajar yang biasanya dilakukan di ruang kelas sekarang diaplikasikan secara Daring di rumah dengan orang tua sebagai pendamping. Tujuan penelitian ini adalah untuk mendapatkan informasi mengenai dampak pandemi Covid-19 terhadap motivasi belajar Daring siswa Sekolah Dasar dan melihat apakah pembelajaran Daring pada level dasar efektif dilakukan. Penelitian ini menggunakan penelitian deskriptif dengan pendekatan kuantitatif yang dilakukan untuk menggali dan mengambarkan suatu obyek penelitian. Populasi dalam penelitian ini seluruh siswa kelas III Sekolah Dasar Negeri se-Gugus I Abai Siat Dharmasraya yang berjumlah 4 sekolah yang memiliki total keseluruhan 245 siswa. Metode survei yang digunakan dalam penelitian menggunakan teknik Proportionate Stratified Random Sampling. Hasil penelitian menunjukan bahwa Covid-19 berpengaruh secara parsial terhadap motivasi belajar daring siswa SD Negeri se-Gugus 1 Abai Siat Dharmasraya dengan t-hitung sebesar 2.477 sedangkan t-tabel sebesar 1.977 dan juga berdampak secara silmultan dengan nilai f-hitung lebih besar dari f-tabel yaitu 5,68 > 2,67. Kata Kunci: Pandemi Covid-19, Motivasi Belajar Daring